2015
DOI: 10.4077/cjp.2015.bad279
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Double Strand Break Repair Gene XRCC3 Genotypes to Nasopharyngeal Carcinoma Risk in Taiwan

Abstract: The DNA double strand break repair protein XRCC3 plays a central role in removing double strand breaks from the genome and defects in cellular repair capacity is closely related to human cancer initiation. Therefore, we aimed to investigate the contribution of XRCC3 genotypes to individual nasopharyngeal carcinoma (NPC) susceptibility. In this hospital-based population research, the genotyping and analyzing of XRCC3 rs1799794, rs45603942, rs861530, rs3212057, rs1799796, rs861539, rs28903081 in a large Taiwanes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Hence, we examined the genotypes of several DNA DSB repair genes, such as X-Ray Repair Cross Complementing 3 (XRCC3) , XRCC6 , XRCC7 , which are involved in the DSB repair system. The associations of these DNA repair genes with multiple types of cancer and diseases, including nasopharyngeal carcinoma [ 41 ], lung cancer [ 42 ], leiomyoma [ 43 ], breast cancer [ 44 ], hepatocellular carcinoma [ 45 ], and especially TNBC [ 46 ], have been explored in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, we examined the genotypes of several DNA DSB repair genes, such as X-Ray Repair Cross Complementing 3 (XRCC3) , XRCC6 , XRCC7 , which are involved in the DSB repair system. The associations of these DNA repair genes with multiple types of cancer and diseases, including nasopharyngeal carcinoma [ 41 ], lung cancer [ 42 ], leiomyoma [ 43 ], breast cancer [ 44 ], hepatocellular carcinoma [ 45 ], and especially TNBC [ 46 ], have been explored in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to crucial role played by this heterodimer in several steps of HR (binding of DNA, resolution of Holiday junctions) [12], a polymorphism affecting its formation may thus influence the capacity of the whole HR DNA repair machinery and play its role in cancer development. Evidence in favor of this hypothesis is, still, rather scarce, as in addition to our previous study in which the Xrcc3 94 His allele was found to be associated with increased risk of HNC [46], only four other studies investigating the association between 94 Arg/His SNP and risk of various cancers exist [60][61][62][63]. These studies were, however, conducted in Taiwanese population completely lacking any variability at this locus, so they failed to provide any valuable information on plausible role of rs3212057 in cancer risk modulation.…”
Section: Discussionmentioning
confidence: 81%
“…In the case of studies conducted by Mittal et al [33], no direct relationship was found between the occurrence of rs1799796 polymorphism in XRCC3 and the incidence of bladder cancer. In addition, the studied polymorphism seems to be not related to the incidence of nasopharyngeal cancer as well as head and neck cancer [27, 34]. However, a meta-analysis of 5302 cases of ovarian cancer compared to 8075 control cases revealed statistically significant correlation of rs1799794 and rs1799796 polymorphism in XRCC3 and an increased risk of developing ovarian cancer in Caucasians, Asian, and African population [35].…”
Section: Discussionmentioning
confidence: 99%